2018
DOI: 10.1093/mnras/sty1842
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of wind-driven protoplanetary nebulae – I. near-infrared emission

Abstract: To understand how the circumstellar environments of post-AGB stars develop into planetary nebulae, we initiate a systematic study of 2D axisymmetric hydrodynamic simulations of protoplanetary nebula (pPN) with a modified ZEUS code. The aim of this first work is to compare the structure of prolate ellipsoidal winds into a stationary ambient medium where both media can be either atomic or molecular. We specifically model the early twin-shock phase which generates a decelerating shell. A thick deformed and turbul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The shock introduces turbulence consistent with the simulations of atomic winds with strong radiative cooling (e.g. Novikov & Smith 2018). Examination of early-stage outputs in the simulation reveals that material driven outwards by the expanding outflows passes through this shock and then becomes disorganised.…”
Section: A Single Orbiting Atomic Jet At High Resolutionsupporting
confidence: 65%
“…The shock introduces turbulence consistent with the simulations of atomic winds with strong radiative cooling (e.g. Novikov & Smith 2018). Examination of early-stage outputs in the simulation reveals that material driven outwards by the expanding outflows passes through this shock and then becomes disorganised.…”
Section: A Single Orbiting Atomic Jet At High Resolutionsupporting
confidence: 65%
“…With the current data available, we cannot trace the excitation mechanism of the molecular gas in NGC 6543's LISs and spectroscopic follow-up observations are needed. UV-fluorescence emission (Black & van Dishoeck 1987;Sternberg & Dalgarno 1989;Burton et al 1990) as well as thermal H 2 emission from shock-heated gas (Hollenbach & McKee 1989;Burton et al 1992;Smith 1995;Novikov & Smith 2018) can explain the values obtained for the LISs in this nebula ( Figure 6).…”
Section: Marquezmentioning
confidence: 54%
“…In the top panel, we show pre-PNe (orange circles), PNe (blue circles), and candidates PNe (gray circles) gathered from the literature (Geballe et al 1991;Aspin et al 1993;Vicini et al 1999;Hora et al 1999;Lumsden et al 2001;García-Hernández et al 2002;Davis et al 2003;Kelly & Hrivnak 2005;Likkel et al 2006;Ramos-Larios et al 2008;Gledhill & Forde 2015;Marquez-Lugo et al 2015;Jones et al 2018). Model predictions of the R(H 2 ) ratio obtained from UV irradiated cloud models (photodissociation regions; Sternberg & Dalgarno 1989;Burton et al 1990) and shock models (Smith 1995;Novikov & Smith 2018) are indicated as red and green vertical stripes, respectively.…”
Section: Marquezmentioning
confidence: 99%
“…In Paper I (Novikov & Smith 2018) we began a systematic E-mail: i-novikov@hotmail.com † E-mail: M.D.Smith@kent.ac.uk study of this transition phase via numerical simulations of molecular and atomic interactions. These are performed with molecular cooling and chemistry which turns out to be crucial to the resulting shell structure.…”
Section: Introductionmentioning
confidence: 99%